2004
DOI: 10.1182/blood.v104.11.635.635
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase Promotes the Spontaneous Metastasis of Myeloma Cells to Bone.

Abstract: Although widespread skeletal dissemination is a critical step in the progression of myeloma, little is known regarding mechanisms that control this process. High levels of the syndecan-1 heparan sulfate proteoglycan are present in the myeloma microenvironment where they bind numerous growth factors (e.g., HGF, FGF-2) that control myeloma growth, angiogenesis and dissemination. Heparanase-1 (HPSE1) is an enzyme that cleaves heparan sulfate chains of proteoglycans and thus may regulate heparan-binding growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 0 publications
1
29
0
1
Order By: Relevance
“…More convincing, direct evidence for a role of heparanase-1 in tumour metastasis was provided by the conversion of non-metastatic murine T-lymphoma and melanoma cells into highly metastatic cells, following transfection with human heparanase-1 cDNA [53]. Similar results were obtained upon over-expression of human heparanase-1 in pancreatic cancer [120], myeloma [132] and breast carcinoma [134] cells. Enhancement of metastasis was even more pronounced for a readily secreted and membrane-bound chimeric form of the enzyme [135].…”
Section: Tumour Metastasismentioning
confidence: 81%
See 1 more Smart Citation
“…More convincing, direct evidence for a role of heparanase-1 in tumour metastasis was provided by the conversion of non-metastatic murine T-lymphoma and melanoma cells into highly metastatic cells, following transfection with human heparanase-1 cDNA [53]. Similar results were obtained upon over-expression of human heparanase-1 in pancreatic cancer [120], myeloma [132] and breast carcinoma [134] cells. Enhancement of metastasis was even more pronounced for a readily secreted and membrane-bound chimeric form of the enzyme [135].…”
Section: Tumour Metastasismentioning
confidence: 81%
“…This observation was confirmed by the finding that increased expressions of heparanase-1 mRNA and protein correlate with increased heparanase activity and the metastatic capacity of rat and human breast cancer cells [53,54]. Since then, this correlation has been observed in a variety of human tumour-derived cell lines and tissues, including those of the bladder [119], pancreas [120], cervix [121], colon [122], ovary [123], endometrium [124], prostate [83], thyroid [125], liver [126], oesophagus [110], stomach [109], oral cavity [127], galbladder [128], nasopharynx [129], brain [130], salivary gland [131] and in multiple myeloma [132] and acute myeloid leukaemia [133]. Consistently, as already mentioned above, elevated levels of heparanase-activity have been detected in sera and urine samples of patients suffering from an aggressive metastatic disease [100][101][102].…”
Section: Tumour Metastasismentioning
confidence: 99%
“…Several studies have demonstrated that the expression level of heparanase is correlated with the grade, metastatic activity, and growth rate of malignant tumors. [33][34][35][36][37] In the study by Uno et al, 24 heparanase expression was specifically inhibited in a dose-dependent manner when T.Tn human esophageal cancer cells and A549 human lung cancer cells were infected with Ad-AS/hep. As a result, the invasion ability of transfected cells decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme breaks down the polysaccharide barrier, facilitating cancer-cell invasion through the vascular basement membrane; also angiogenesis and metastases are promoted [93]. In humans elevated heparanase expression by the tumor has been correlated with a more aggressive behavior in breast, colon, ovary, pancreas, non-small lung cancer, acute myeloid leukemia, and myeloma tumors [94][95][96][97][98][99][100][101]. Heparanase also cleaves the growth factor bearing heparan sulfate groups from heparan sulfate proteoglycans in the extracellular matrix and cellular membranes [102][103][104].…”
Section: Cancer and Heparinsmentioning
confidence: 99%